2020
DOI: 10.3389/fpubh.2020.570676
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Socio-Behavioral-Metabolic Risk Profiles and Associated Factors for Chronic Diseases of Lifestyle in Urban and Rural Communities in Central South Africa

Abstract: Background: The global escalating prevalence of lifestyle-related non-communicable diseases places a significant burden on health systems. Chronic diseases of lifestyle (CDL) are a group of diseases that share similar modifiable risk factors that can result in long-term disease processes. Considering the socio-behavioral-metabolic risk profiles of communities and risk factors predictive of the presence of CDL can assist in the development of focused and effective community-based prevention, interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 39 publications
2
10
5
Order By: Relevance
“…Regarding fetal complications, our study found statistically significant relation between obesity and incidence of fetal complications(p value =0.012).one of these fetal complications were macrosomia and high birth weight >3500gm. 12% of our cases delivered macrosomic infants .our study agreed with a previous study made by Dai et al, (2018) which found that pre-pregnancy obesity should be considered as an important risk factor for macrosomia [25]. 9% of our cases delivered infant with congenital anomalies.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding fetal complications, our study found statistically significant relation between obesity and incidence of fetal complications(p value =0.012).one of these fetal complications were macrosomia and high birth weight >3500gm. 12% of our cases delivered macrosomic infants .our study agreed with a previous study made by Dai et al, (2018) which found that pre-pregnancy obesity should be considered as an important risk factor for macrosomia [25]. 9% of our cases delivered infant with congenital anomalies.…”
Section: Discussionsupporting
confidence: 92%
“…The high number of staff who reported no existing comorbidities (69%) is similar to a study comparing HCWs and non-HCWs in terms of severity of disease which reported HCWs to be more healthy and less likely to be hospitalised and had less severe symptoms 46,47 . The proportion of staff (31.2%) reporting co-morbidities correlates with reported comorbidities among the general South African population, namely diabetes and or high blood pressure 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…These NCDs, commonly referred to as chronic diseases (CDs), include cardiovascular disease, cancer, chronic respiratory disease and diabetes, and represent a growing global burden, accounting for seven out of ten deaths worldwide [2]. Current projections will rank NCDs among the top 10 causes of death worldwide by 2040, and the leading cause of death in the African region by 2030 [3] of which the large *Corresponding author: salihamharchi@gmail.com proportion of these deaths is related to cardiovascular diseases followed by cancerous and metabolic diseases [4]. All share key behavioral risk factors that can be modified, including physical inactivity, smoking, alcohol consumption, and high fat intake [5].…”
Section: Introductionmentioning
confidence: 99%
“…All share key behavioral risk factors that can be modified, including physical inactivity, smoking, alcohol consumption, and high fat intake [5]. These risk factors (RF) lead to physiological and metabolic changes such as obesity, hypertension, hyperglycemia and hyperlipidemia and are at the origin of certain chronic pathologies mainly cardiovascular diseases, certain types of cancer and diabetes mellitus [3]. A recent study showed that low-and middle-income countries had the highest risk of dying from CD, particularly in Africa, Central Asia and Eastern Europe [6].…”
Section: Introductionmentioning
confidence: 99%